10m+8=6m-10

Simple and best practice solution for 10m+8=6m-10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10m+8=6m-10 equation:


Simplifying
10m + 8 = 6m + -10

Reorder the terms:
8 + 10m = 6m + -10

Reorder the terms:
8 + 10m = -10 + 6m

Solving
8 + 10m = -10 + 6m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-6m' to each side of the equation.
8 + 10m + -6m = -10 + 6m + -6m

Combine like terms: 10m + -6m = 4m
8 + 4m = -10 + 6m + -6m

Combine like terms: 6m + -6m = 0
8 + 4m = -10 + 0
8 + 4m = -10

Add '-8' to each side of the equation.
8 + -8 + 4m = -10 + -8

Combine like terms: 8 + -8 = 0
0 + 4m = -10 + -8
4m = -10 + -8

Combine like terms: -10 + -8 = -18
4m = -18

Divide each side by '4'.
m = -4.5

Simplifying
m = -4.5

See similar equations:

| 1/4(72-6a)=-30 | | x*7=1200 | | 168=150(1+0.08) | | 3(x-3)+2=26 | | 580.586=2*3.14*18.49+2*3.14*4.3*h | | -3+8(1-2x)=4x-15 | | 3k+y=1 | | 2w+6x-y+8w-21x-7y= | | 95r=1995 | | -69v=-3450 | | (2+0.50)=10 | | 2=(0.50+10) | | 4q-9=27 | | 2(f-3)+9=5+f-1 | | 2-3x(8-6)= | | c=399+.06*399 | | 2y+1=1.5y+3 | | k-48=-6 | | T=.18*12.38 | | 2x+6=12x-12 | | 2(2+8v)= | | y+a=-21 | | .12=.15-.05x | | (2x+9(2))+(1x-5(2))=50 | | 188.9024=6.28r^2+20.069r | | -4n+6(5n-1)=72 | | 5y-6=-29 | | 64.8+18t+4.9t^2=0 | | ((2)2x+9)+((2)1x-5)=50 | | x^2-6-5=0 | | 975=25N | | x-378=0 |

Equations solver categories